2015
DOI: 10.1021/jacs.5b06178
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Impact of Reaction Paths on Mechanical Degradation of Intercalation Cathodes for Lithium-Ion Batteries

Abstract: The intercalation compounds are generally considered as ideal electrode materials for lithium-ion batteries thanks to their minimum volume expansion and fast lithium ion diffusion. However, cracking still occurs in those compounds and has been identified as one of the critical issues responsible for their capacity decay and short cycle life, although the diffusion-induced stress and volume expansion are much smaller than those in alloying-type electrodes. Here, we designed a thin-film model system that enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…More importantly, the mechanical degradation of Na 3 V 2 (PO 4 ) 3 /C cathode material driven by structure nanocrystallization is the major reason for the more serious capacity fading of Na 3 V 2 (PO 4 ) 3 /C in Na-Zn hybrid aqueous rechargeable battery than that in Zn-ion battery. Cracking induced capacity fading has been confirmed in several lithium ion intercalation cathodes (layered LiCoO 2 , spinel LiMn 2 O 4 , spinel LiNi 0.5 Mn 1.5 O 4 , olivine LiFePO 4 ), which display volume changes only 2 % -7% during Li + ion extraction/insertion [30][31][32][33][34] . Compared to Li ions ( r Li + = 0.73 Å ) and Zn ions ( r Zn 2+ + = 0.74 Å ), the ionic radius of Na ions ( r Na + = 1.13 Å ) is much larger and seems to impact the host structure of electrode more severely during Na + extraction/insertion.…”
Section: Resultsmentioning
confidence: 91%
“…More importantly, the mechanical degradation of Na 3 V 2 (PO 4 ) 3 /C cathode material driven by structure nanocrystallization is the major reason for the more serious capacity fading of Na 3 V 2 (PO 4 ) 3 /C in Na-Zn hybrid aqueous rechargeable battery than that in Zn-ion battery. Cracking induced capacity fading has been confirmed in several lithium ion intercalation cathodes (layered LiCoO 2 , spinel LiMn 2 O 4 , spinel LiNi 0.5 Mn 1.5 O 4 , olivine LiFePO 4 ), which display volume changes only 2 % -7% during Li + ion extraction/insertion [30][31][32][33][34] . Compared to Li ions ( r Li + = 0.73 Å ) and Zn ions ( r Zn 2+ + = 0.74 Å ), the ionic radius of Na ions ( r Na + = 1.13 Å ) is much larger and seems to impact the host structure of electrode more severely during Na + extraction/insertion.…”
Section: Resultsmentioning
confidence: 91%
“…Striking inhomogeneity in the strain distribution throughout the particle was also reported. Further evidence was provided by in situ multi-beam optical stress sensor on LMNO thin-film electrodes, which showed that the stress in LMNO increases with lithium removal and it can reach up to 126 MPa at fully delithiated state (MNO)48. Strain survey on Li x MNO crystals was not feasible with FF-TXM as the contrast mechanism of the technique is not sensitive to the local crystal structure distortion.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is still unable to claim that these stresses are reasons for mechanical degradation in lithium-ion batteries. As Dr. Nancy Dudney has pointed out, 51 mechanical failure should not be a concern for intercalation-type cathodes, since the volume change upon cycling is only 2-7%, much smaller than that in alloying-type anodes which is typically 100%. Moreover, Christensen and Newman 23 have showed that a compressive external stress could reduce the likelihood of particle fracture because the fracture threshold for the tensile stress is typically much lower than that for the compressive stress.…”
Section: Resultsmentioning
confidence: 99%